FOMO (FEAR OF MISSING OUT) AND GEN-Z'S EXCESSIVE CONSUMPTION: ANALYSIS OF THE INTERPRETATION OF Q.S. AL-ISRA' VERSES 26-27 ON THE PROHIBITION OF ISRAF - Hamzah Muchtar, Evan (Jurnal Asy-Syukriyyah, 2025)
The Fear of Missing Out (FOMO) phenomenon has become a prominent issue among college students, especially in the context of a consumerist lifestyle influenced by social media. College students often feel pressured to follow consumption trends such as using branded goods, visiting popular places, and attending big events, even though they are expensive and sometimes lead to israf (wasteful) behavior. This article aims to analyze the FOMO phenomenon and excessive consumption from the perspective of the interpretation of QS. Al-Isra’ verses 26–27, which emphasize the prohibition of waste and the importance of managing resources wisely. The research approach used is qualitative with literature studies and secondary data from various sources, including social media observations. The results of the analysis show that the FOMO phenomenon can be associated with the influence of social media that encourages college students to consume excessively, which is contrary to Islamic teachings on simplicity and managing sustenance. Education based on Islamic values, such as qana’ah and sharia financial literacy, is the key to overcoming this problem. This study suggests the importance of an educational approach to introduce an Islamic consumer lifestyle among students, so that they can be wiser in using resources and avoiding waste.